Clinical-functional and immune-microbiological features of the oral cavity in children and adolescents with chronic forms of gingivitis - Axmadovich, Sobirov Alijon; Amrulloevich, Gafforov Sunnatullo; Tukhtakhujaevna, Nurmatova Nodira; Sotvoldievich, Djambilov Ravshan; Xaldarovna, Yakubova Farida; Matlubovich, Radjabov Nodirxon; Sunnatulloyevna, Gafforova Sabina; Nusratovich, Ibragimov Faxriddin (Edelweiss Applied Science and Technology, 2025)
It is known that inflammatory periodontal diseases (IPD) rank second among dental diseases and are widespread across all population categories regardless of age, place of residence, or gender. It is also known that the transition from gingivitis to periodontitis begins with the appearance of a specific group of oral cavity pathogens, among which P. gingivalis, Actinobacillus actinomycetemcomitans, Treponema denticola, and others play a significant role. Local causes of IPD include poor oral hygiene, improper techniques and use of basic and additional oral care products, frequent consumption of soft foods, and an excess of easily fermentable carbohydrates. Currently, the prevalence of IPD has sharply increased and continues to rise, with a growing trend among younger individuals. Based on the above, this study examines the clinical-functional and immunomicrobiological state of the oral cavity, including the gingival sulcus, in children and adolescents suffering from catarrhal and hypertrophic gingivitis. A total of 425 children and adolescents were selected for the study, including those with chronic catarrhal gingivitis (n=195, CCG) and chronic hypertrophic gingivitis (n=165, CHG), as well as practically healthy children (n=65, control group – CG). Based on the established diagnosis, the clinical-functional and immunomicrobiological state of the oral cavity, including the gingival sulcus, was examined in children and adolescents with various forms of gingivitis. It was found that children and adolescents with CCG and CHG exhibited poor oral hygiene, which worsened with age. Severe inflammatory processes in the gums were observed in all children and adolescents with chronic gingivitis, particularly catarrhal gingivitis. Additionally, local circulatory disorders in the gums were noted, accompanied by increased vascular tone, decreased peripheral resistance to blood flow, reduced vascular elasticity, and impaired blood rheology. Furthermore, β-hemolytic streptococci of group A were identified as the predominant microorganisms in the gingival sulcus and oral cavity, along with a significant increase in the proportion of Candida spp., particularly Candida albicans. Immune status disorders were also detected, characterized by increased IgG, IgA, and IgM concentrations in the blood. A correlation was observed between the quantitative indicators of microorganisms in oral fluid and gingival sulcus contents in patients with CCG and CHG. Based on the OHI-S and PLI indices, as well as caries indicators of primary and permanent teeth in patients with CCG, poor oral hygiene was evident (p <0.0001). The results of various functional and clinical assessments suggest that patients with CCG and CHG exhibit local circulatory disorders in chronic disease progression. These disorders are accompanied by increased vascular tone, while β-hemolytic streptococci of group A and Candida albicans frequently dominate in the gingival sulcus and oral cavity. Additionally, a correlation was found between local immune status, particularly among children aged 10–13 years.